Hubungan Obesitas, Stres Dengan Kejadian Hipertensi Pada Usia Dewasa Muda Di Wilayahpuskesmas Sumbersari Kota Metro - Dian Utama Pratiwi Putri; M. Inggil Prasetyo; Achmad Djamil (Universitas Malahayati Lampung, 2021)
ABSTRACT :CORRELATION OF OBESITY, STRESS WITH HYPERTENSION IN YOUNG ADULTS AT SUMBERSARI’S PUBLIC HEALTH CENTER DISTRICT METRO CITY 2020 Background: Hypertension is a condition of a person suffering from an increase in blood pressure above normal, namely systolic blood pressure ≥ 140 mmHg and or diastolic blood pressure ≥ 90 mmHg. Based on data from the Sumbersari Metro City Health Center 2019, the number of hypertension cases increased from 833 people in 2018 to 1134 people. Most people with hypertension who visited Sumbersari Health Center were according to age groups, namely at the age of 20-44 years as many as 488 people.purpose: To determine the relationship between obesity and stress and the incidence of hypertension in young adults in the area of Puskesmas Sumbersari, Metro City in 2020.Methods: This was a quantitative study, cross sectional design. Independent variables (obesity, stress) and bound variables (hypertension). The population of this study were all 1427 patients who visited the public examination center at Sumbersari’s Public Health center Metro City, 94 samples taken by accidental sampling. Direct data collection from respondents. Data analysis was univariate and bivariate (chi square) with an alpha of 0.05.Results: The results showed that from 94 respondents, 55 (58.5%) of respondents had hypertension, 36 (38.3%) of respondents were obese and as many as 54 (57.4%) of respondents were in the stress category.Conclusion: From the two independent variables studied, there was a relationship with hypertension, namely obesity (p-value 0.003: 95% CI) with an OR value of 6.6 and stress (p-value 0.000: 95% CI) with an OR value of 5.8. . It is recommended that health workers educate respondents to reduce stress such as listening to music, relaxation with aromatherapy or other coping mechanisms. Encouraging hypertensive patients to be able to lose weight, by adjusting the diet, exercising regularly every day and weighing each month. Keywords: Obesity, Stress, Hypertension INTISARI : HUBUNGAN OBESITAS, STRES DENGAN KEJADIAN HIPERTENSI PADA USIA DEWASA MUDA DI WILAYAH PUSKESMAS SUMBERSARI KOTA METRO TAHUN 2020 Pendahuluan: Hipertensi merupakan suatu keadaan seseorang yang menderita peningkatan tekanan darah di atas normal, yaitu tekanan darah sistolik ≥ 140 mmHg dan atau tekanan darah diastolik ≥ 90 mmHg. Berdasarkan data Puskesmas Sumbersari Kota Metro 2019 angka kasus hipertensi meningkat dari tahun 2018 sebanyak 833 orang menjadi 1134 orang. Penderita hipertensi yang berkunjung ke Puskesmas Sumbersari terbanyak menurut kelompok umur yaitu pada umur 20-44 tahun sebesar 488 orang.Tujuan:Diketahui hubungan obesitas dan stres dengan kejadian hipertensi pada usia dewasa muda di wilayah Puskesmas Sumbersari Kota Metro Tahun 2020.Metode: Jenispenelitiankuantitatif, desin / rancangancross sectional. Variabel bebas (obesitas, stres) dan Variabel Terikat (hipertensi). Populasi dari penelitian ini adalah seluruh pasien yang berkunjung ke balai pemeriksaan umum Puskesmas Sumbersari Kota Metro sebanyak 1427 orang, sampel sebanyak 94 diambil secara accidental sampling. Pengumpulan data langsungkepadaresponden.Analisis data secaraunivariatdanbivariat (chi square) dengan alfa 0,05.Hasil Penelitian: Hasil penelitian didapatkan bahwa dari 94 responden, sebanyak 55 (58,5%) responden mengalami hipertensi, sebanyak 36 (38,3%) responden obesitas dan sebanyak 54 (57,4%) responden dengan kategori stres. Kesimpulan: Dari dua variabel bebas yang diteliti terdapat hubungan dengan kejaidan hipertensi yaitu variabel obesitas (p-value 0,003 :CI 95%) dengan nilai OR 6,6 dan Stres (p-value 0,000 :CI 95%) dengan nilai OR 5,8.Disarankan petugas kesehatan mengedukasi responden untuk mengurangi stres seperti mendengarkan musik, relaksasi dengan aroma terapi atau mekanisme koping lainnya. Menganjurkan pasien hipertensi untuk dapat mengurangi berat badan, dengan mengatur menu makan, berolahraga rutin setiap hari dan melakukan penimbangan berat badan setiap bulan. Kata Kunci : Obesitas, Stres, Hipertensi